Dual-Wavelength Thulium Ytterbium Co-Doped Fiber Laser - Hazlihan Haris; Ahmad Razif Muhammad; Norazlina Saidin; Mohd Shahnan Zainal Abidin; Hamzah Arof; Mukul Chandra Paul; Sulaiman Wadi Harun (Institute of Advanced Engineering and Science, 2017)
We report on the generation of dual-wavelength fiber laser peaking at 1990.64 and 1998.92 nm with a simple ring cavity setup. The lasers are demonstrated using a fabricated silica-based nano-engineered octagonal shaped double-clad Thulium-Ytterbium co-doped fiber (TYDF) as a gain medium in a simple all-fiber ring configuration. By using 980 nm multimode laser, a stable dual-wavelength laser is generated at a threshold pump power of 1500 mW due to the non-polarization rotation (NPR) effect occurred in the cavity. The effect has been self-controlled by a suppression of mode competition in the gain medium. The result shows that the slope efficiency of the generated dual–wavelength laser is measured to be 27.23%. This dual-wavelength TYDF laser operated steadily at room temperature with a 34 dB optical signal-to-noise ratio. Keywords: Dual-wavelength fiber laser, nano-engineered glass, silica-based TYDF, NPR effect.